Employee Training Data Collection Information System at PT. Pelindo I (Persero) - Rizaldy Khair; Ibrahim (INFOKUM, 2020)
Employees are company assets because their role determines whether the company succeeds in achieving its goals. In acquiring employees who perform well the company must hold the implementation of training, which serves to improve the ability of employees to work. This research was conducted on employees of the Directorate of Human Resources and General Affairs of PT Pelindo 1 (Persero) Jl Krakatau Ujung, Medan. Referring to this, training data collection is also carried out manually using ms excel which is considered still ineffective because they have to look at the data to one source of training organizers, namely the Corporate University Division so that if there are employees who are in branches outside the city they will find it difficult to see what training they will get, there is a system that can make it easier for employees to see their own training data online. The system uses a MySQL Database with 11 tables and also uses the CodeIgniter Framework and php programming language. The training data displayed using Bootstrap to speed up and facilitate website development, to be able to see the existing training data users must enter the training data feature first and search according to the name, year or branch.